Combined anodic and cathodic peroxide production in an undivided carbonate/bicarbonate electrolyte with 144% combined current efficiency - Schanz, Tobias; Stöckl, Markus; Burek, Bastien O.; Holtmann, Dirk; Bloh, Jonathan Z. (Frontiers in Catalysis, 2024)
In recent years, the electrochemical synthesis of peroxides has attracted renewed interest as a potential environmentally friendly production compared to the established anthraquinone process. In addition, it is possible to produce the peroxides directly on site, eliminating the need for expensive and hazardous transportation and storage. Cathodic production of hydrogen peroxide from oxygen is already quite well developed. Anodic production from water, on the other hand, is still facing significant challenges, despite its historic pioneering role. In this manuscript we show that anodic and cathodic synthesis of peroxides can even be combined to achieve greater than 100 % current efficiency (CE) due to the combined effect of both half-reactions. So far, similar devices have always employed different electrolytes for each, which necessitated the use of a membrane and posed contamination risk. However, herein we show that both half-reactions can also employ the same electrolyte. This enables even an undivided cell, omitting the need for the expensive membranes. Despite its simplicity, this setup yielded an outstanding performance with a combined CE of 144%.